An Affair not to Remember? It Might Help to Change Your Name - ZHANG, Man Cyndi (Institutional Knowledge at Singapore Management University, 2013)
While a growing body of research has examined how organizations respond to institutional change, less examined is how institutional change can create opportunities for organizations to manage their public image. We propose that institutional change allows firms to leverage the ambiguity around the motive for image management and thus minimize audience’s unfavorable attribution of the motive. Specifically, we focus on an organization’s name change as a means of image management. From the audience’s standpoint, an organization could change its name as a result of having responded to institutional change, or to convey new strategic directions, or to manipulate the public perception. Institutional change allows a window of opportunity when audiences are confronted with the ambiguity over the motive for name change. Based on this framework, we predict that firms with poor image are more likely to engage in name change during institutional change, and that they are more likely to engage in the type of name change that indicates new strategic direction to further benefit from the ambiguity. Similarly, we also predict that name changes engaged this way are likely to generate more favorable market reactions. We test our framework in the context of the name change by publicly listed Chinese firms during the government-mandated corporate governance reform.